Studies on Peculiar Observations of the Food and Feeding Habits of Painted Pebble Crab Leucosia anatum South East Coast of India - Varadharajan, D (International Journal of Pharmaceutical & Biological Archive, 2012)
Studies on Peculiar Observations of the Food and Feeding Habits of Painted Pebble Crab Leucosia anatum South East Coast of India